1992
DOI: 10.1088/0964-1726/1/3/005
|View full text |Cite
|
Sign up to set email alerts
|

Active plate and wing research using EDAP elements

Abstract: The deflection characteristics of Structures using directionally attached piezoelectric (OAP) and enhanced OAP (EDAP) elements are explored. Tests demonstrate that piezoceramic elements, which are isotropic, exhibit orthotropic behavior when directionally attached using any of three methods: (i) partial attachment, (ii) transverse shear lag, and (iii) differential stiffness bonding. Test results demonstrate that directional enhancement through transverse stiffening can increase OAP element strain from 5 to 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…Because the fin was intended for use in a TOW missile, it was capable of ±5° deflections with a corner frequency better than 30Hz and a maximum power consumption under 50mW. [12][13][14] During the this program, an important design philosophy was evolved that is still seen as critical advice for adaptive aerostructures designers to this day: i. Minimize the amount of work done by adaptive materials on passive structure ii.…”
Section: Early Fin and Wing Designsmentioning
confidence: 99%
“…Because the fin was intended for use in a TOW missile, it was capable of ±5° deflections with a corner frequency better than 30Hz and a maximum power consumption under 50mW. [12][13][14] During the this program, an important design philosophy was evolved that is still seen as critical advice for adaptive aerostructures designers to this day: i. Minimize the amount of work done by adaptive materials on passive structure ii.…”
Section: Early Fin and Wing Designsmentioning
confidence: 99%
“…[20]- [21] For a conventional bimorph actuator element this results in the following bending stiffness coefficient, D l , and coupling stiffness coefficient, B a :…”
Section: Analytical Modelmentioning
confidence: 99%
“…[12][13][14] The resulting Constrained Spar Torque-Plate Missile Fin effort demonstrated ±4.5°s tatic deflections with no aeroelastic divergence problems or use of aeroelastic amplification methods. This project represented the first time an adaptive aerostructure was built with collocated elastic axis, lines of aerodynamic centers and centers of gravity.…”
Section: Supporting Munitions Projectsmentioning
confidence: 99%
“…Chief among them was the realization that low aspect ratio flight control surfaces which were designed to carry full high α, high speed flight loads could not be made to actively deform enough to achieve suitable levels of flight control, even when using 10% strain actuation levels associated with shape-memory alloys for structural materials. Rather, it was shown that gross structural rotational deflections of entire flight control surfaces were necessary to achieve forces and moments which were usable for most classes of subsonic and supersonic missiles (projects [10][11][12][13][14][15][16][17]. Figure 3 shows a 2% thick double circular arc supersonic missile fin undergoing a camber deformation beside a NACA 0012 subsonic missile fin being actively deformed in twist.…”
Section: Supporting Munitions Projectsmentioning
confidence: 99%